Developing an early screening guide for jihadi terrorism: A behavioural analysis of 30 terror attacks. Issue 1 (January 2017) - Neo, Loo Seng; Khader, Majeed; Ang, Jansen; Ong, Gabriel; Tan, Eunice
Abstract This study seeks to develop a screening guide for jihadi terrorism with the intention of streamlining the huge amounts of raw intelligence into smaller amounts of data for further analysis. On the basis of the authors' collective experience in dealing with terrorists, and a review of the literature and pre-attack indicators developed by law enforcement agencies worldwide, 53 features of jihadi terrorism belonging to three domains (behaviour ideology, group psychology and operational preparatory) were identified. These features were then mapped against 30 jihadi attacks from different parts of the world. The frequency distribution of each feature across the 30 attacks were analysed using Pearson'sχ 2 test. Three significant features were identified: (i) individuals pushing for terrorist ideals through violence; (ii) individuals showing a desire for revenge; and (iii) the presence of a leader figure who espouses terrorist ideology. Results further revealed that features from the behaviour-ideology domain had higher prevalence estimates across the 30 attacks. Recommendations are made for operationalising these features as a potential early screening guide for the interpretation of data.